Ionic conductivity of LiMn₂.ₓFe₁0₄ materials / Badrul Amin Abdullah - Abdullah, Badrul Amin (2011)
LiMn2.xFex04 materials with different stoichiometric value (x = 0.1, 0.2, 03) powders were synthesized via a Self-propagating combustion, (SPC) method by using nitrates of the metal or transition metal as a precursor. The thermal analysis was performed by using Setsys Evolution 1750 (TGA-DSC 1500) in order to determine the annealing temperature. The powders then annealed at the temperature 800°C for 30 hours to remove all of the moisture. The crystal structure and purity also ionic conductivityj o of the materials were then investigated and characterized by X-ray diffraction (XRD) and ax. impedance using Electrochemical Impedance Spectroscopy, (EIS) respectively. XRD results indicate that pure single phase of cubic crystal structure had been obtained for the materials. EIS results then indicate that the ionic conductivity, a of the materials increasing with the increasing of temperature by following the Arrhenius law. At temperature 373K, LiMn1.7Feo.3O4 has the highest ionic conductivity, a with 3.81 x 10"4 S.cm'1. Overall, it had been noticed that by insertion of Fe atom, the ionic conductivity, a of LiMn204 was increased by the degree of 2 which is from 10"6 S.cm"1 to 10"4 S.cm"1.